Sensitive and selective Cu2+ detection via surface plasmon resonance using ionophore decorated nanocrystalline cellulose-graphene oxide thin film - Daniyal, Wan Mohd Ebtisyam Mustaqim Mohd; Fen, Yap Wing; Abdullah, Jaafar; A. Bakar, Ahmad Ashrif; Mahdi, Mohd Adzir (Elsevier, 2024)
In this work, highly sensitive and selective surface plasmon resonance (SPR) sensor has been developed using nanocrystalline cellulose-graphene oxide-ionophore (NCC-GO-ionophore) for copper ion (Cu2+) detection. By incorporating SPR with nanocrystalline cellulose-graphene oxide-ionophore (NCC-GO-ionophore) thin film, Cu2+ was able to be detected as low as 0.001 ppm until 0.1 ppm. Moreover, the results show that the NCC-GO-ionophore thin film has good sensitivity towards Cu2+ with sensitivity value of 59.9150° ppm−1 from 0.001 to 0.01 ppm and 2.2261° ppm−1 from 0.01 to 0.1 ppm. Besides that, the developed sensor also shows high affinity towards Cu2+ compared to other metal ions. Using the Langmuir isotherm model, the binding affinity constant, K was calculated i.e., 6.881 × 103 M−1. Furthermore, the ability of the sensor to detect Cu2+ in spiked river water sample was also investigated where Cu2+ as low as 0.5 until 100 ppm can be determined. This result shows that the sensor has high sensitivity and selectivity towards Cu2+ detection.